High rates of general practice attendance by former prisoners: a prospective cohort study. Issue 2 (17th July 2017) - Carroll, Megan; Spittal, Matthew J; Kemp‐Casey, Anna R; Lennox, Nicholas G; Preen, David B; Sutherland, Georgina; Kinner, Stuart A
Abstract: Objectives: To determine the rates at which people recently released from prison attend general practitioners, and to describe service users and their encounters. Design, participants and setting: Prospective cohort study of 1190 prisoners in Queensland, interviewed up to 6 weeks before expected release from custody (August 2008 – July 2010); their responses were linked prospectively with Medicare and Pharmaceutical Benefits Scheme data for the 2 years after their release. General practice attendance was compared with that of members of the general Queensland population of the same sex and in the same age groups. Main outcome measures: Rates of general practice attendance by former prisoners during the 2 years following their release from prison. Results: In the 2 years following release from custody, former prisoners attended general practice services twice as frequently (standardised rate ratio, 2.04; 95% CI, 2.00–2.07) as other Queenslanders; 87% of participants visited a GP at least once during this time. 42% of encounters resulted in a filled prescription, and 12% in diagnostic testing. Factors associated with higher rates of general practice attendance included history of risky opiate use (incidence rate ratio [IRR], 2.09; 95% CI, 1.65–2.65), having ever been diagnosed with a mental disorder (IRR, 1.32; 95% CI, 1.14–1.53), and receiving medication while in prison (IRR, 1.82; 95% CI, 1.58–2.10). Conclusions: Former prisoners visited general practice services with greater frequency than the general Queensland population. This is consistent with their complex health needs, and suggests that increasing access to primary care to improve the health of former prisoners may be insufficient, and should be accompanied by improving the quality, continuity, and cultural appropriateness of care.